2019
DOI: 10.3389/fmars.2019.00266
|View full text |Cite
|
Sign up to set email alerts
|

Air-Sea Heat Flux Variability in the Southeast Indian Ocean and Its Relation With Ningaloo Niño

Abstract: Previous studies suggest that both air-sea heat flux anomalies and heat advection caused by an anomalous Leeuwin Current play an important role in modulating the sea surface temperature (SST) variability associated with the Ningaloo Niño. However, the estimates of surface heat fluxes vary substantially with the datasets, and the uncertainties largely depend on the time scale and locations. This study investigates air-sea flux variability associated with the Ningaloo Niño using multiple datasets of surface flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The definition is based on daily SST data but was modified here to use monthly output fields from the global ocean simulations. The adapted approach employed the Ningaloo Niño index (NNI), which has been used previously to study MHWs off the coast of WA (Kataoka et al 2014(Kataoka et al , 2017(Kataoka et al , 2018Marshall et al 2015;Feng et al 2015;Feng and Shinoda 2019). We adapt the NNI definition by Marshall et al (2015), who use the average SST anomalies over the box region 1108-1168E, 228-328S.…”
Section: Extreme Event Detection and Validationmentioning
confidence: 99%
“…The definition is based on daily SST data but was modified here to use monthly output fields from the global ocean simulations. The adapted approach employed the Ningaloo Niño index (NNI), which has been used previously to study MHWs off the coast of WA (Kataoka et al 2014(Kataoka et al , 2017(Kataoka et al , 2018Marshall et al 2015;Feng et al 2015;Feng and Shinoda 2019). We adapt the NNI definition by Marshall et al (2015), who use the average SST anomalies over the box region 1108-1168E, 228-328S.…”
Section: Extreme Event Detection and Validationmentioning
confidence: 99%
“…During La Niña years (e.g., 1999-2000, 2011-2012) the LC flows stronger resulting in transport of elevated ocean temperatures down the west coast (Feng et al, 2003). The region is typically dominated by strong southerly wind patterns through the summer months that oppose the LC, contributing to its seasonality, and also acting to moderate heating of coastal ocean temperatures through upwelling (Woo et al, 2006;Rossi et al, 2013) and air-sea heat flux (e.g., evaporative cooling) processes (Feng and Shinoda, 2019). However, relaxation or reversal of the southerly winds can further enhance heating, as occurred during the La Niña event of 2010-2011, when weak, northerly winds combined with an unusually strong summer Leeuwin Current to elevate summer maximum sea temperatures by 2-4 • C in the region.…”
Section: Introductionmentioning
confidence: 99%
“…The Agulhas Current has a seasonal cycle and is strongest in summer (Krug and Tournadre, 2012;Beal and Elipot, 2016) and tied to a baroclinic adjustment of near-field winds (Hutchinson et al, 2018). Seasonal changes in the Agulhas retroflection region (Lutjeharms and van Ballegooyen, 1988;Quartly and Srokosz, 1993) and in the southwest Indian Ocean (Ffield et al, 1997) have been suggested from hydrographic and satellite data (Krug and Tournadre, 2012), but with weak statistical significance due to a lack of a sufficiently long time series.…”
Section: Western Boundarymentioning
confidence: 99%